2014
DOI: 10.1159/000362948
|View full text |Cite
|
Sign up to set email alerts
|

The Glucocorticoid Dexamethasone Inhibits U937 Cell Adhesion and Neutrophil Release via RhoA/ROCK1-Dependent and Independent Pathways

Abstract: Aims: The aim of the present study was to investigate the role of the Ras homolog family member A (RhoA)/Rho-associated coiled-coil-containing protein kinase 1 (ROCK1) signaling pathway in the inhibition of inflammatory responses by the glucocorticoid dexamethasone (Dex). Methods: The inhibitory effects of Dex and Rho-kinase inhibitor fasudil (Fas) on phorbol ester-induced release of O2- and MPO from neutrophils and on U937 mononuclear cell adhesion were examined along with the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In agreement with this result, the enhanced activity of p38 MAP and the decreased activity of ERK1/2 and JNK were investigated in CMSP-treated B16-F1 cells. GTPase-RhoA and PKC are known upstream activators of cellular MAPK pathways, and [31][32][33][34]. We found that treatment of B16-F1 cells with CMSP caused decreased levels of GTPRhoA but led to no changes in p-PKC.…”
Section: Discussionmentioning
confidence: 73%
“…In agreement with this result, the enhanced activity of p38 MAP and the decreased activity of ERK1/2 and JNK were investigated in CMSP-treated B16-F1 cells. GTPase-RhoA and PKC are known upstream activators of cellular MAPK pathways, and [31][32][33][34]. We found that treatment of B16-F1 cells with CMSP caused decreased levels of GTPRhoA but led to no changes in p-PKC.…”
Section: Discussionmentioning
confidence: 73%
“…RhoA plays important pathophysiological roles in the cardiovascular system and in disease states such as hypertension, heart failure, stroke, diabetes and others [22,23]. We found that RhoA activation and geranylgeranylation of RhoA in the tissue of the heart increased at week 6 of SHR although there was no significant difference, but it significantly increased at week 12 of SHR (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…We showed that the oAβ [25][26][27][28][29][30][31][32][33][34][35] injection-induced inhibition of sAPPα and ADAM10 is associated with an activation of ROCK/PDK1 pathways. 68,75,76 ROCK activity seems to be directly upregulated by GC, 72,73,77 and ROCK/PDK1 activation after oAβ [25][26][27][28][29][30][31][32][33][34][35] is reversed by treatment with CORT113176, again constituting a vicious cycle based on feed-forward effects on GR signaling (Figure 7). 68,75,76 ROCK activity seems to be directly upregulated by GC, 72,73,77 and ROCK/PDK1 activation after oAβ [25][26][27][28][29][30][31][32][33][34][35] is reversed by treatment with CORT113176, again constituting a vicious cycle based on feed-forward effects on GR signaling …”
Section: F I G U R Ementioning
confidence: 99%
“…These results are consistent with several studies showing that ROCKs modulate the shedding of sAPPα through an inhibition of tumor necrosis factor-α-converting enzyme (TACE or ADAM) activity, and that ROCKs depletion reduces Aβ levels. 68,75,76 ROCK activity seems to be directly upregulated by GC, 72,73,77 and ROCK/PDK1 activation after oAβ [25][26][27][28][29][30][31][32][33][34][35] is reversed by treatment with CORT113176, again constituting a vicious cycle based on feed-forward effects on GR signaling (Figure 7). ROCK also affect Tau hyperphosphorylation.…”
Section: F I G U R Ementioning
confidence: 99%